Physiological psychology: The Biology of human bahavior - McFarland, Richard (California: Mayfield, 1981)
Contiene: Basic neurophysiology. Neuroanatomy. Psychoanatomy: concepts and methods. Genetics. Gathering information and organizing responses. Vision. Five sensory systems. Attention, sleep and wakefulness. Sexual motivation and behavior. Hunger and thirst. Emotions Remembering
Keywords: Psicología